Active and total prokaryotic communities in dryland soils. Issue 1 (26th June 2013) - Angel, Roey; Pasternak, Zohar; Soares, M. Ines M.; Conrad, Ralf; Gillor, Osnat
Abstract The relationship between total and metabolically active soil microbial communities can change drastically with environment. In dry lands, water availability is a key factor limiting cells' activity. We surveyed the diversity of total and active Archaea and Bacteria in soils ranging from arid desert to Mediterranean forests. Thirty composited soil samples were retrieved from five sites along a precipitation gradient, collected from patches located between and under the dominant perennial plant at each site. Molecular fingerprinting was used to site‐sort the communities according of their 16S rRNA genes (total community) and their rRNA (active community) amplified by PCR or RT‐PCR from directly extracted soil nucleic acids. The differences between soil samples were much higher in total rather than active microbial communities: differences in DNA fingerprints between sites were 1.2 and 2.5 times higher than RNA differences (for Archaea and Bacteria, respectively). Patch‐type discrepancies between DNA fingerprints were on average 2.7–19.7 times greater than RNA differences. Moreover, RNA‐based community patterns were highly correlated with soil moisture but did not necessarily follow spatial distribution pattern. Our results suggest that in water‐limited environments, the spatial patterns obtained by the analysis of active communities are not as robust as those drawn from total communities.